Instrumentation of off-the-shelf ultrasound system for measurement of probe forces during freehand imaging. (23rd January 2019) - Schimmoeller, Tyler; Colbrunn, Robb; Nagle, Tara; Lobosky, Mark; Neumann, Erica E.; Owings, Tammy M.; Landis, Benjamin; Jelovsek, J. Eric; Erdemir, Ahmet
Abstract: Ultrasound is a popular and affordable imaging modality, but the nature of freehand ultrasound operation leads to unknown applied loads at non-quantifiable angles. The purpose of this paper was to demonstrate an instrumentation strategy for an ultrasound system to measure probe forces and orientation during freehand imaging to characterize the interaction between the probe and soft-tissue as well as enhance repeatability. The instrumentation included a 6-axis load cell, an inertial measurement unit, and an optional sensor for camera-based motion capture. A known method for compensation of the ultrasound probe weight was implemented, and a novel method for temporal synchronization was developed. While load and optical sensing was previously achieved, this paper presents a strategy for potential instrumentation on a variety of ultrasound machines. A key feature was the temporal synchronization, utilizing the electrocardiogram (EKG) feature built-in to the ultrasound. The system was used to perform anatomical imaging of tissue layers of musculoskeletal extremities and imaging during indentation on an in vivo subject and an in vitro specimen. The outcomes of the instrumentation strategy were demonstrated during minimal force and indentation imaging. In short, the system presented robust instrumentation of an existing ultrasound system to fully characterize the probe force, orientation, and optionally its movement during imaging while efficiently synchronizing all data. Researchers may use the instrumentation strategy on any EKG capable ultrasound systems if mechanical characterization of soft tissue or minimization of forces and deformations of tissue during anatomical imaging are desired.